Two scales to measure suicide prevention communication among Latino parents: how do U.S.-born and foreign-born parents compare? - Villarreal-Otálora, Tatiana; Collete, Tyler; McPherson, Jane (Frontiers in Psychology, 2025)
IntroductionThis study validates two adapted versions of the Parental Suicide Prevention Communication Self-Efficacy scale (PSPCSE) for Latino parents of adolescents in the U.S.: the PSPCSE-Lat-E for predominately English speakers and the PSPCSE-Lat-S for Spanish speakers. These scales aim to measure suicide-related prevention communication self-efficacy (SPCSE) among Latino parents.MethodsResearchers adapted the PSPCSE to address lethal-means safety and incorporated culturally sensitive language to devise the PSPCSE-Lat-E (11-items), which was then translated and back-translated to create the PSPCSE-Lat-S (11-items). Both scales were included in a 60-question survey that also gathered demographic data, prevention programming preferences, familism levels, and suicide literacy. Participants were recruited through online panels and social media, resulting in responses from 220 foreign-born and 414 U.S.-born Latino parents (N = 634). An exploratory factor analysis examined the PSPCSE-Lat-E and PSPCSE-Lat-S psychometric properties.ResultsAnalysis (N = 634) revealed distinct structures: a two-factor structure for the English (48.8% variance, ω=.88) versus a three-factor for the Spanish (51.6% variance, ω=.82) in the rotated models. PSPCSE-Lat-E respondents reported higher confidence in discussing suicide content, while PSPCSE-Lat-S respondents showed greater comfort with emotional support items. PSPCSE-Lat-S suicide items demonstrated exceptional discrimination despite lower means, suggesting heightened cultural sensitivity among these parents.DiscussionFindings indicate that the PSPCSE-Lat-E and PSPCSE-Lat-S are reliable and valid tools for assessing Latino parent’s SPCSE. These scales can now be used in clinical and community settings, offering significant implications for health providers and future research. Differences in prevention tasks between foreign-born and U.S.-born Latino parents necessitate tailored interventions.